TYPOLOGICAL PROBLEMS OF MEDICAL TEXTS AND TERMS FROM ENGLISH INTO UZBEK - pcadmin, Movlanova Ra’no (Scholar Express Journal, 2025)
Medical translation is one of the most challenging fields of translation studies due to its specialized terminology, complex syntactic structures, and the necessity for accuracy. This article examines the typological problems encountered in translating medical texts and terms from English into Uzbek. The primary focus is on linguistic and cultural differences, terminological inconsistencies, and syntactic variations that pose challenges for translators. The study also highlights the need for standardized medical terminology in Uzbek to ensure clarity and precision in translation. Through comparative analysis, the article explores strategies to overcome these challenges and proposes solutions for enhancing the quality of medical translations
Keywords: medical translation; typological problems; medical terminology